Pengaruh Electronic Word Of Mouth dan Beauty Influencer terhadap Purchase Decision dengan Value Co-Creation sebagai Variabel Intervening: Studi pada Konsumen GLAD2GLOW di Kota Semarang - Tsaniya Salma Sadida; Sri Rahayu Tri Astuti (Faculty of Economics and Business Diponegoro University, 2025)
The shift in lifestyle dynamics in the era of modernity has heightened public awareness of the importance of maintaining healthy skin. This increased awareness has driven the growth of Indonesia’s beauty industry, as seen in the rising popularity of skincare brands such as Glad2Glow, which has gained traction in the Indonesian market. This study aims to examine the influence of Electronic Word of Mouth (e-WOM) and beauty influencers on purchase decisions, with value co-creation serving as a mediating variable. The research was conducted on 185 consumers in Semarang City who have purchased Glad2Glow products. Data were collected through a questionnaire using purposive sampling and analyzed using Structural Equation Modeling (SEM) with the AMOS 21 software. The findings indicate that both e-WOM and beauty influencers have a positive and significant effect on purchase decisions. Furthermore, value co creation also positively influences purchase decisions and mediates the relationship between e-WOM, beauty influencers, and purchase decisions. These results support all proposed hypotheses and provide insights for Glad2Glow to enhance consumer engagement and purchasing behavior.